Rapid prototyping in the development of optical pickup unit - Hong, Kian Hui. (2008)
Rapid prototyping has proven itself in the electronics industry to cut down the product development time cycle. In the development of the Optical Pickup Unit (OPU), extremely high precision is needed to make a functional model. Very often, in the design phase of the product development cycle, the prototype of the OPU is machined form a single piece of aluminium block to make the working sample.